Aplicación web de la gestión del programa semillero de investigadores de la Espam MFL - Avellán Zambrano, Nerina Víctoría (2015)
Considering the development of a web application for managing the PSI (Seed Program Researcher) ESPAM of MFL, held optimal processes influencing the determination of the scientific vocation of students and their attitudes; Because of this an analysis by a Stage 0 that began with the pre-registration program was then a selection of beneficiaries was performed using an online test that was done to students who previously made the nomination, once immersed in the selection, start the part of teachers which is in effect three stages detailed as follows (initial training, project development and implementation of projects I + D + i); so that later the results are shown as the culmination of projects and reports R + D + I at the annual scientific conference held by the CIC (Coordination of Scientific Research). Compression technique for the development of the above the MIDAS methodology focused on the development of Web applications are used, it consists of four phases (MIDAS / SD (Requirements and System Architecture) MIDAS / HT (prototype system), MIDAS / DB (database) MIDAS / FC (SERVICES AND LOGIC SYSTEM)), enabling out a proper sequence of processes in the development of the application, and the use of tools such as Bootstrap within the Visual Studio IDE 2010, SQL Server 2008 and 2012, Photoshop, 3-tier architecture, programming language C #, HTML5, javascript and CSS gave the user friendly approach.